Penerapan Model Pembelajaran Kooperatif Tipe TAI (Team Assisted Individualization) Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis - Gusasi, Magvira; Zakaria, Perry; Achmad, Novianita (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The ability to understand concepts is highly needed to master each topic in mathematics, which is systematic, rational, and structured through interrelated subtopics. The purpose of this study is to improve students’ knowledge of basic mathematical principles on the topics of squares and rectangles by applying a cooperative learning model based on TAI (Team Assisted Individualization) during learning activities in class VII-3 at SMP Negeri 1 Tilongkabila in the even semester of the 2024/2025 academic year, with a total of 26 students. Data collection procedures were carried out using measurement instruments in the form of observation sheets for teacher activities, observation sheets for student activities, and tests of students’ skills in understanding basic mathematical principles. The type of research used was Classroom Action Research (CAR) with four main stages: planning, implementation, observation, and reflection. The findings indicate that implementing classroom action in two cycles using the TAI approach can improve students’ conceptual understanding in mathematics, as shown by increased teacher and student activities and improved completeness in students’ skill test results.